Reduction In Skeletal Muscle Chloride Conductance Improves Contractile Force In Wildtype, But Not In Hyperkalemic Periodic Paralysis Mice - Higgins, Amanda (Université d'Ottawa / University of Ottawa, 2014)
Hyperkalemic periodic paralysis (HEPP) is an inherited, autosomal disorder characterized by myotonia and periodic paralysis in skeletal muscle. The hallmark of the disease is a severe sensitivity to the K+-induced force depression, the cause of the paralysis. Previous studies have provided evidence that the sensitivity to the K+-induced force depression can be alleviated when the Cl- conductance (GCl) is lowered. However, those studies were carried out at non-physiological temperatures (25°-30°C) and few stimulation frequencies. The overarching goal of this study was to examine whether manipulating GCl pharmacologically was a viable target for treating HEPP. This work sought to document the interactive effect of K+ and Cl- on force development in mouse skeletal muscle at 37°C, over a wide range of stimulation frequencies. Secondly, experiments were undertaken to determine if a reduction in GCl could protect against the severe K+ sensitivity in HEPP. The results show that in wildtype muscle, a reduction in GCl improved force generation at high [K+]e at stimulation frequencies that naturally occur in vivo for mouse EDL and soleus. While the effect in wildtype muscles was proof of principle that a reduction in GCl may be a potential approach to treat HEPP patients, the effects of reduced GCl at high [K+]e was quite variable in HEPP muscles. In a few cases, lowering GCl did improve force generation at high [K+]e. However, in most cases the decrease in GCl exacerbated the force depression at high [K+]e, suggesting that more studies will be necessary to understand the variability in the Cl- effect to conclude whether a decrease in GCl is a viable approach to treat HEPP patients.
Keywords: Chloride conductance; Hyperkalemic Periodic Paralysis; Channelopathy; Skeletal muscle